EFFECTS USING OF ZEOLITE INTO RATIONS TO RATION CONSUMPTION, GROWTH, AND DRESSING PERSENTAGE OF MALE LOCAL RABBITS - Sulastri Sulastri (Jurnal Zeolit Indonesia, 2007)
This research was conducted 6 weeks to study the effect of zeolit in ration on feed consumption, average daily gain (growth rate), and dressing percentage of male local rabbits. Twenty four rabbit were used in this research designed by randomized completely block design. The treatment of research were level of zeolit on ration that was 0.0; 2.5; 5.0; 7.5 % of dry matter. This research indicated that zeolit didn't affect (P>0.05) on feed consumption, average daily gain, and dressing percentage. The average of feed consumption was highest (87,15 ± 4,52 gram ) on rabbits that got ration with 2.5 % zeolit. The average daily gain was highest (17,14 ± 0,82 gram) on rabbits that got ration without zeolit. The average of dressing percentage was highest (48,58 ± 3,56 %) on rabbit that got ration with 2,5 % zeolite. It could be concluded that zeolit on ration didn't affect on feed consumption, average daily gain (growth rate), and dressing percentage of male local rabbits.